MILLENNIAL PERCEPTION TOWARDS THE PURCHASE DECISIONS OF GREEN PRODUCTS –A DESCRIPTIVE STUDY - Vasuki, K.; SHOBA; V., Balaji (International Journal of Research -GRANTHAALAYAH, 2021)
The study is executed to assess the millennial perception towards the purchase decisions of green products in Chennai city. The study used both primary and secondary data. The secondary data obtained through research articles, magazines, and daily newspapers. The primary data was gathered from the millennial that are purchasing the green products in Chennai city. The sample size of the study is 591. A simple convenience sampling method was used. The study found that the factors i.e., Environmentally Friendly, Environmental Responsibility, Healthy, Natural products, and environmentally protection, and Social Appeal significantly influenced green products’ purchase decisions among the millennial in the study region. The study also originates that there is significant difference among the age group of concerning the purchase decisions of green products certain aspects like Environmentally friendly, and Healthy. The study results also exhibited that the male and female millennial have similar perception on purchase of green products in the study region.